2016
DOI: 10.1615/critrevoncog.2016016976
|View full text |Cite
|
Sign up to set email alerts
|

Resistance to Cell Death and Its Modulation in Cancer Stem Cells

Abstract: Accumulating evidence has demonstrated that human cancers arise from various tissues of origin that initiate from cancer stem cells (CSCs) or cancer-initiating cells. The extrinsic and intrinsic apoptotic pathways are dysregulated in CSCs, and these cells play crucial roles in tumor initiation, progression, cell death resistance, chemo- and radiotherapy resistance, and tumor recurrence. Understanding CSC-specific signaling proteins and pathways is necessary to identify specific therapeutic targets that may lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
106
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 115 publications
1
106
0
Order By: Relevance
“…Resistance to apoptosis is a hallmark of CSCs . We therefore evaluated whether miR‐26b‐5p plays any role in regulating apoptosis of HCC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Resistance to apoptosis is a hallmark of CSCs . We therefore evaluated whether miR‐26b‐5p plays any role in regulating apoptosis of HCC cells.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, FEZF1‐AS1 knockdown decreased the expression of stem factors (Nanog, Oct4, SOX2). It is well‐known that cancer‐stem like cells endow the growth or proliferation potential in residual surgical resection or post‐chemoradiotherapy (Liu, Choi, et al, ; Lo, Wolfson, & Zhou, ; Mansoori, Madjd, Janani, & Rasti, ; Safa, ). Therefore, our results revealed that FEZF1‐AS1 could promote the BCSC properties through positively accelerating the stemness.…”
Section: Discussionmentioning
confidence: 99%
“…CD133 and Oct‐4A, the CSC markers, have been suggested as protectors for cancer cells from apoptosis induced by chemotherapeutic agents . Significantly increased apoptosis‐related proteins—cleaved caspase‐3 and cleaved PARP—were observed in cells treated with gemcitabine plus thiostrepton (Figure C).…”
Section: Resultsmentioning
confidence: 98%
“…CD133 and Oct-4A, the CSC markers, have been suggested as protectors for cancer cells from apoptosis induced by chemotherapeutic agents. 25,26,36 Significantly increased apoptosis-related proteins-cleaved caspase-3 and cleaved PARP-were observed in cells treated with gemcitabine plus thiostrepton ( Figure 4C). Apoptosis induced by gemcitabine plus thiostrepton was more significant compared with that induced by gemcitabine or thiostrepton alone ( Figure 4C).…”
Section: Thiostrepton and Gemcitabine Synergistically Suppresses Nsmentioning
confidence: 96%